Answer:
Option A. 4, 4.5, 5, 5.5
Step-by-step explanation:
Left point: a=x=4
Right point: b=x=6
Range: r=b-a→r=6-4→r=2
Width of each of the four equal intervals: w=2/4→w=0.5
The first left endpoint is x1=a→x1=4
The second left endpoint is x2=x1+w→x2=4+0.5→x2=4.5
The third left endpoint is x3=x2+w→x3=4.5+0.5→x3=5
The fourth left endpoint is x4=x3+w→x4=5+0.5→x4=5.5
Then, the list is: x1, x2, x3, x4 = 4, 4.5, 5, 5.5
Hey there!
Since 2 goes into 8, you would simplify. You would get 1 inch and 4 miles. Next, set up a ratio. The ratio is 1 inch: 4 miles. So for every inch on the map, there is 4 miles.
I hope this helps!
Answer:
165°
Step-by-step explanation:
11π/12 * 180/π = 1980π/12π
Reduce & Cancel: 165°
Answer:
(c-a, 0)
Step-by-step explanation:
The horizontal space between (c, b) and P is the same as the space between (a, b) and O.
Coordinates are written (x, y), where x is for horizontal space.
P is on the x-axis, making the y-coordinate 0.
(a+c, 0) would be to the right of the entire parallelogram.
(c, 0) would be directly below (c, b).
(a-c, 0) would be to the left of the entire parallelogram and in the other quadrant.
Answer :
![6{y}^{4} {z}^{2} + 12 {y}^{3} {z}^{2}-3 {y}^{3} {z}+3 {y}^{2} {z}^{2}](https://tex.z-dn.net/?f=6%7By%7D%5E%7B4%7D%20%7Bz%7D%5E%7B2%7D%20%2B%2012%20%7By%7D%5E%7B3%7D%20%7Bz%7D%5E%7B2%7D-3%20%7By%7D%5E%7B3%7D%20%7Bz%7D%2B3%20%7By%7D%5E%7B2%7D%20%7Bz%7D%5E%7B2%7D)
Step-by-step explanation :
To find the product of
![3 {y}^{2} z(2 {y}^{2} z + 4yz - y + z)](https://tex.z-dn.net/?f=3%20%7By%7D%5E%7B2%7D%20z%282%20%7By%7D%5E%7B2%7D%20z%20%2B%204yz%20-%20y%20%2B%20z%29)
First we expand the bracket ,
it implies that, we use the expression outside the bracket to multiply individual expressions inside the bracket.
Hence
![3 {y}^{2} z(2 {y}^{2} z + 4yz - y + z)](https://tex.z-dn.net/?f=%203%20%7By%7D%5E%7B2%7D%20z%282%20%7By%7D%5E%7B2%7D%20z%20%2B%204yz%20-%20y%20%2B%20z%29)
![= 3 {y}^{2} z(2 {y}^{2} z) + 3 {y}^{2} z(4yz) - 3 {y}^{2} z(y )+3 {y}^{2} z( z)](https://tex.z-dn.net/?f=%20%3D%203%20%7By%7D%5E%7B2%7D%20z%282%20%7By%7D%5E%7B2%7D%20z%29%20%2B%203%20%7By%7D%5E%7B2%7D%20z%284yz%29%20-%203%20%7By%7D%5E%7B2%7D%20z%28y%20%29%2B3%20%7By%7D%5E%7B2%7D%20z%28%20z%29)
we now apply the law of indices
![{a}^{m} \times {a}^{n} = {a}^{m+n}](https://tex.z-dn.net/?f=%20%7Ba%7D%5E%7Bm%7D%20%5Ctimes%20%7Ba%7D%5E%7Bn%7D%20%3D%20%7Ba%7D%5E%7Bm%2Bn%7D)
meaning, when you are multiplying two expressions with the same bases , repeat one of the bases and add the exponents.
Then, simplify to obtain